The complete mitochondrial genome of a wild-collected Kappaphycus malesianus (Solieriaceae, Rhodophyta) - Bea A. Crisostomo; Richard V. Dumilag; Michael Y. Roleda; Arturo O. Lluisma (Mitochondrial DNA. Part B. Resources, 2023)
Kappaphycus malesianus is a red seaweed farmed primarily for its carrageenan, a polysaccharide important in the food and pharmaceutical industries. Among the commercially cultivated Kappaphycus species, only K. malesianus has no mitogenome data available. Here, we assembled the mitochondrial genome of K. malesianus from next-generation sequencing data. The circular mitogenome consisted of 25,250 base pairs (bp) with a GC content of 30.25%. These values were comparable to previously sequenced solieriacean mitogenomes. Structural features, such as the stem-loop and hairpin, which were previously reported in other rhodophytes mitochondrial DNA, were also identified. The annotated genes (24 protein-coding genes, 24 tRNA genes, and 2 rRNA genes) were arranged in an order similar to the other available solieriacean mitogenomes. Lastly, phylogenetic analysis using 23 predicted protein domains showed the sister relationship of K. malesianus with other Kappaphycus species.